ACUTE PAIN'S NURSING PROBLEM OR NURSING DIAGNOSIS IN HYPERTENSIVE PATIENTS BASED ON SDKI AND SIKI: A CASE STUDY - Muhammad Taufiq Hidayat; Dimas Anjar Kuncoro; Eko Prasetya W (UPT Penerbitan Universitas Jember, 2022)
Background: Complications of Hypertension due to hypertension can be suppressed with an appropriate, effective, and efficient nursing process approach, by knowing more specifically the signs and interventions. However, research on this matter is still very limited. Objectives: Identify signs and symptoms of major/minor acute pain nursing problems in hypertensive patients and identify the implementation of independent nursing actions to overcome these problems. Methods: This study uses a descriptive research design with a secondary data analysis approach sourced from nursing care documentation of 20 respondents in project reports of the D3 Nursing Study Program UNEJ for the period 2018 to 2020. Data on major/minor signs and symptoms, as well as the implementation of actions independent nursing care (based on SDKI and SIKI) identified, are presented in the distribution table for further discussion. Results: There are 6 major and minor signs of acute pain problems according to the SDKI that most often appear, namely complaining of pain, grimacing, restlessness, unable to complete activities, increased blood pressure, and changes in appetite and there are also 9 interventions that most often appear, namely: Identification Location, duration, frequency, quality, the intensity of pain Identify pain scales Identify knowledge and beliefs about pain Provide non-pharmacological techniques to reduce pain Facilitate rest and sleep Explain causes, periods and triggers of pain Explain strategies pain reliever, Teach non-pharmacological techniques to reduce pain. Conclusion: Knowing the most dominant symptoms and signs, complaints of increased pain, and blood pressure can be done with the right intervention, effective and efficient.